EFFECTS OF SMOKING IN UROTHELIAL CARCINOMA OF BLADDER UNDERGOING RADIAL CYSTECTOMY - MASOOD, A; KHAN, RMFUR; RAZA, QH; AKHTAR, M; HASSAN, S; ASLAM, N (Biological and Clinical Sciences Research Journal, 2023)
The current study was designed to evaluate the impact of smoking status and cessation in bladder carcinoma patients undergoing radial cystectomy. A prospective study was conducted in the Department of Urology and Radiation Oncology of Shifa International Hospital, Islamabad and MMDC, Multan from January 2022-January 2023. A total of 190 patients with urothelial carcinoma of the bladder undergoing radial cystectomy were included in the study. Smoking history was noted for each patient before radial cystectomy. This history included smoking status, quantity, duration, and cessation in patients with former smoking history. The mean age of patients was 65.3 years. Among 190 patients, 87 were former smokers, 65 were current, and 38 were non-smokers. 58 patients (30.5%) had a pathological tumor stage 3. Multivariate analysis showed that duration of smoking, smoking cessation, and cumulative smoking exposure were predictors of tumor staging. Patients with more than 30 years of smoking were at higher odds of developing advanced tumor stage. Similarly, increased cumulative exposure was associated with greater odds of high tumor stage (p<0.001). Duration of smoking cessation had an opposite relationship with the odds of advanced tumor (p=0.001). Based on the results, it can be concluded that the current smoking status and cumulative smoking exposure are directly associated with disease development and recurrence in urothelial carcinoma of bladder patients. Smoking cessation has the opposite relationship respectively.